PERAN MITOS KOYEIDABA DALAM MEMBENTUK PANDANGAN HIDUP MASYARAKAT SUKU MEE PAPUA - Happy Dwi Prihartanti; Harjito (STKIP Subang, 2025)
This study examines the role of the Koyeidaba Myth in shaping the worldview of the Mee Tribe in Papua. The Koyeidaba Myth is a messianic narrative transmitted orally and regarded as a source of moral values, social ethics, and the concept of salvation for the Mee people. This research employed a descriptive qualitative method with data collected through interviews, observations, and documentation involving tribal elders, religious leaders, and local residents in Topo Village, Nabire. The findings reveal that the Koyeidaba Myth significantly influences the Mee people's understanding of life, particularly regarding the values of abundance (mobu), safety (aji), respect for nature, and adherence to moral principles such as prohibitions against killing, stealing, lying, jealousy, and adultery. The myth also serves as a conceptual bridge between traditional Mee beliefs and Christianity. However, the study found a generational shift in which younger Mee individuals no longer know the story in full, although they still practice its underlying values. This research concludes that the Koyeidaba Myth is a fundamental structure that maintains the identity, morality, and worldview of the Mee community